Puesta en marcha de la planta de compostaje en la sede Ecocampus de la Universidad de América (2024)
Through this study, a literature review and technical procedures for in-situ and laboratory measurements are proposed to determine the appropriate process for starting up the composting plant at the Universidad de América Ecocampus, evaluating factors such as the quantity and quality of organic waste. To meet the stated objective, alternatives were evaluated and a literature review was conducted to determine the best compost production process, taking into account physical conditions such as pH, temperature and humidity, as well as other factors related to cost and benefit.